Which Colleges Increase Voting Rates? - D'Wayne Bell; John B. Holbein; Samuel J. Imlay; Jonathan Smith (Institute of Labor Economics (IZA), 2024)
We study how colleges shape their students' voting habits by linking millions of SAT takers to their college-enrollment and voting histories. To begin, we show that the fraction of students from a particular college who vote varies systematically by the college's attributes (e.g. increasing with selectivity) but also that seemingly similar colleges can have markedly different voting rates. Next, after controlling for students' college application portfolios and pre-college voting behavior, we find that attending a college with a 10 percentage-point higher voting rate increases entrants' probability of voting by 4 percentage points (10 percent). This effect arises during college, persists after college, and is almost entirely driven by higher voting-rate colleges making new voters. College peers' initial voting propensity plays no discernible role.
Keywords: I23; I26; D72; 330; college choice; returns to college; civic engagement; voting